Penerapan Terapi Rendam Kaki Menggunakan Sereh untuk Menurunkan Hipertensi pada Lansia di RW 24 Batursari, Mranggen Demak - Kristyowati Kristyowati; Sonhaji Sonhaji (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The study aimed to analyze cases of management in hypertensive patients with a therapeutic intervention of lemongrass warm foot bath on the reduction of blood pressure. The writing design used is a case report. Participants in the preparation of case reports with medical diagnosis of hypertension, The focus of the study in this study is clients with nursing and diagnosis problems, namely clients who experience increased blood pressure with hypertension. The research instruments used were observation of blood pressure of hypertension patients and nursing care reports. The research was carried out at RW 24 Batursari, Mranggen Demak. The time for data collection is for the first and second patients on November 5, 2024 – November 07, 2024 with the length of data collection time to be carried out on patients, which is a minimum of 3 days of treatment. Based on the results of the final evaluation on both subjects, all of these diagnoses were successfully resolved. Diagnoses that were successfully completed in the first subjects included acute pain, impaired physical mobility, knowledge deficit, and risk of falls. Meanwhile, the diagnoses that were successfully overcome in the second subject were acute pain, sleep pattern disorders, knowledge deficits, and spiritual distress.